Evaluasi Program Pendidikan dalam Meningkatkan Keterampilan Kreativitas Siswa di SMPN 3 Krian - Andita, Reykha Zatri Puteri; Azzahro, Fathimah; Putri, Berlian Therapi Herdian; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
Evaluation activities are comparing what has been achieved from a program with what should be achieved based on established standards/criteria. In principle, program evaluation is an integral part of educational evaluation in general. The type of research used by researchers is a qualitative approach, with data collection carried out to find out the problems faced and to design solutions. The data collection technique is through literature study. This evaluation makes it possible to identify needs for program improvement and development to make it more effective and efficient in the future.in the main text and should not exaggerate the main conclusions.